PENERAPAN PENDEKATAN KOMUNIKATIF DALAM PEMBELAJARAN BAHASA INDONESIA - Yuliati, Asna (Universitas Islam Darul Ulum, 2016)
The objectives are: (1) to describe the ways teacher applies communicative approach in teaching Indonesian language at the fifth grade of SDN Karangkembang Babat in the academic year 2012/2013 and (2) to know the fifth grade studentsâ competence of SDN Karangkembang Babat in mastering Indonesian language after being taught using communicative approach. This research is a descriptive one. The data of this research are steps applied by the Indonesian language teacher and the scores achieved by the students due to the use of communicative approach in teaching in the classroom. The results of the research show that the procedures of communicative approach involve two methods, namely: (1) task-giving mehod, and (2) asking-answering method. In terms of studentsâ competence, the fifth grade students of SDN Karangkembang can achieve good scores due to the use of communicative method in the process of learning of Indonesian language.